The vulnerables [large type] - Nunez, Sigrid (Thorndike Press large print top shelf, 2024)
"Elegy plus comedy is the only way to express how we live in the world today, says a character in Sigrid Nunez's ninth novel. The Vulnerables offers a meditation on our contemporary era, as a solitary female narrator asks what it means to be alive at this complex moment in history and considers how our present reality affects the way a person looks back on her past. Humor, to be sure, is a priceless refuge. Equally vital is connection with others, who here include an adrift member of Gen Z and a spirited parrot named Eureka. The Vulnerables reveals what happens when strangers are willing to open their hearts to each other and how far even small acts of caring can go to ease another's distress. A search for understanding about some of the most critical matters of our time, Nunez's new novel is also an inquiry into the nature and purpose of writing itself"--